Kemampuan Literasi Teknologi Siswa Kelas X pada Program Keahlian Multimedia: Analysis & Deskripsi - Musalina, Musalina; Tahang, La; Erniwati, Erniwati (Jurnal Penelitian Pendidikan Fisika, 2019)
This study aims to determine the results of students' technological literacy abilities on technical aspects, cognitive aspects and social aspects. The object in this study was class X students on a multimedia expertise program with 100 people. This research uses descriptive-quantitative research methods. The instrument used in this study was a student technology literacy questionnaire. The type of data obtained is quantitative data obtained from the student's technological literacy abilities questionnaire. Data analysis procedures in this study were: (1) calculating the total score from the questionnaire for each student; (2) determine the value of students' technology literacy abilities for each indicator; and (3) categorizing students' technology literacy abilities based on technical, cognitive and social aspects. The results of the technology literacy ability of the tenth grade students of the multimedia expertise program at SMKN 4 Kendari for each aspect, namely the technical aspects, 84.75% are in the good category in the cognitive aspect, 71.06% are in the quite good category. and in the social aspect, 86, 31% are in the very good category. Thus it can be concluded that students' technological literacy skills, especially in the cognitive aspects are still low and need to be improved so that in the future they can compete in technological development. Therefore, further researchers are advised to focus on cognitive aspects.